2013
DOI: 10.1039/c3ra42649a
|View full text |Cite
|
Sign up to set email alerts
|

Naturally and synthetically linked lys48 diubiquitin: a QM/MM study

Abstract: Site-specific chemical conjugates of proteins with ubiquitin-like modifiers are a powerful tool for biochemists to probe the function of these post-translational modifications. As a prominent example, the seven native isopeptide-linked diubiquitins serve as models to study polyubiquitin chains, but not all of them can be prepared by enzymatic means. To date, several approaches to access synthetically conjugated diubiquitins have been reported, however, an experimental structure of such a molecule with an unnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
0
9
0
2
Order By: Relevance
“…To be recognized and processed by DUBs, Ub conjugates bearing non‐native linkages should recapitulate native structural features. The conformations and flexibility of select non‐native Ub linkages have previously been evaluated with computational methods . However, to effectively address whether non‐native linkages can adopt native chain conformations and functions, a solution‐based characterization is needed.…”
Section: Introductionmentioning
confidence: 99%
“…To be recognized and processed by DUBs, Ub conjugates bearing non‐native linkages should recapitulate native structural features. The conformations and flexibility of select non‐native Ub linkages have previously been evaluated with computational methods . However, to effectively address whether non‐native linkages can adopt native chain conformations and functions, a solution‐based characterization is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations using Rosetta, for example, revealed that a disulfide-linked Ub conjugate samples the same conformational space as the native conjugate [35]. On the other hand, molecular dynamics simulations of Ub dimers bearing a triazole linker showed the artificial linker renders the conjugate less flexible compared to the native dimer [36]. These results suggest that the disulfide linkage might not affect the on/off rates of binding interactions while the triazole linker could introduce some deviation.…”
Section: Synthesis Of Defined Ub-substrate Conjugates — An Overviewmentioning
confidence: 99%
“…We next investigated whether connecting the individual ubiquitin moieties with triazoles still results in chains with native-like properties, as it has already been demonstrated for di-ubiquitin by Mootz and co-workers. [20] For this purpose, an antibody that selectively binds K48-linked ubiquitin chains was employed ( Figure S2). Indeed, K48-linked ubiquitin oligomers were detected while no signals could be observed for the other chain linkages.…”
mentioning
confidence: 99%